2010
DOI: 10.1007/s10875-010-9382-9
|View full text |Cite
|
Sign up to set email alerts
|

TL1A Selectively Enhances IL-12/IL-18-Induced NK Cell Cytotoxicity against NK-Resistant Tumor Targets

Abstract: IntroductionTL1A (TNFSF15) augments IFN-γ production by IL-12/IL-18 responsive human T cells. Its ligand, death domain receptor 3 (DR3), is induced by activation on T and NK cells. Although IL-12/IL-18 induces DR3 expression on most NK cells, addition of TL1A minimally increases IFN-γ production.Methods51Chromium release and flow cytometric analysis were used to determine whether the TL1A-DR3 pathway is implicated in tumor cell lysis. Our aim was to determine whether the TL1A-DR3 pathway is implicated in tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 31 publications
(34 reference statements)
2
22
0
Order By: Relevance
“…TL1A biases T cells to differentiate towards Th1 and Th17 phenotype [12], [13], [17] and modulates Treg expansion and functions [18][20]. Moreover, DR3 can modulate NK [6], [21] and NKT-cell functions [22]. Consistently, recent studies have reported an essential role for the TL1A/DR3 pathway in generating T-cell host defense response [23], [24].…”
Section: Introductionmentioning
confidence: 53%
“…TL1A biases T cells to differentiate towards Th1 and Th17 phenotype [12], [13], [17] and modulates Treg expansion and functions [18][20]. Moreover, DR3 can modulate NK [6], [21] and NKT-cell functions [22]. Consistently, recent studies have reported an essential role for the TL1A/DR3 pathway in generating T-cell host defense response [23], [24].…”
Section: Introductionmentioning
confidence: 53%
“…IL-18 is known to activate NK and T cells through its receptor-mediated signaling to produce IFN-γ, contributing to Th1 cell development (50, 67). Additionally, IL-18 enhances NK cell cytotoxicity, Fas ligand-mediated Th1 cell cytotoxicity, and proliferation of activated T cells (67, 68). In the parasite-infected mice, parallel to IL-18 induction, IL-12 is produced at increased levels as infection progresses (see Figs.…”
Section: Discussionmentioning
confidence: 99%
“…TL1A also promotes Treg proliferation and attenuates Treg-mediated suppression of non-regulatory CD4 1 T cells [9]. In addition, TL1A has been shown to costimulate invariant NKT cells [10] and may have a role in enhancing NK cell-mediated tumor cell killing [11]. …”
Section: Introductionmentioning
confidence: 99%